Philosophical footprints in the evolution of art: an analysis of the flourishing of Yangliuqing woodblock New Year prints during the Ming dynasty - Baicheng Qi; Minggang Liu (Trans/Form/Ação)
The philosophical ideas of the Ming dynasty influenced the social and aesthetic changes, as well as the folk beliefs portrayed in Yangliuqing woodblock New Year paintings. Confucianism and other neo-Confucian philosophies, which sought to restore moral order and ritual propriety, heavily influenced the courtly artistic elements that were adopted into these prints. The School of Mind, which was more focused on emotions and individual inspiration, brought a more free and secular approach to the art, thus making folk art more personal. Practical learning promoted the depiction of daily life, which in turn promoted a pragmatic view on art. The unity of knowledge and action (heart-learning), investigating things to attain knowledge (Neo-Confucianism), and the unity of heaven and humanity (Daoism) guided the thematic choices, application of techniques and social functions of these prints. This paper will analyze how these philosophical currents directly influenced the artistic transformation process in the Yangliuqing woodblock New Year paintings and their social functions.